Upfront surgery or definitive radiotherapy for patients with p16-negative oropharyngeal squamous cell carcinoma. A GETTEC multicentric study. Issue 2 (February 2021) - Culié, Dorian; Viotti, Julien; Modesto, Anouchka; Schiappa, Renaud; Chamorey, Emmanuel; Dassonville, Olivier; Poissonnet, Gilles; Guelfucci, Bruno; Bizeau, Alain; Vergez, Sebastien; Dupret-Bories, Agnes; Garrel, Renaud; et al.
Abstract: Introduction: Therapeutic management of oropharyngeal squamous cell carcinomas (OPSCC) is still debated. Since the role of HPV was demonstrated, few studies have focused on HPV-negative OPSCC. The aim of our study was to assess the impact of therapeutic strategy (surgical vs. non-surgical) on oncologic outcomes in patients with HPV-negative OPSCC. Material and method: All p16-negative OPSCCs treated from 2009 to 2014 in 7 tertiary-care centers were included in this retrospective study and were classified according to the therapeutic strategy: surgical strategy (surgery ± adjuvant radiotherapy and chemotherapy) vs. non-surgical strategy (definitive radiotherapy ± chemotherapy). Patients not eligible for surgery (unresectable tumor, poor general-health status) were excluded. Univariate, multivariate and propensity score matching analyses were performed to compare overall (OS), disease-specific (DSS) and recurrence-free survival (RFS). Results: Four hundred seventy-four (474) patients were included in the study (surgical group: 196; non-surgical group: 278). Five-year OS, DSS and RFS were 76.5, 81.3 and 61.3%, respectively, in the surgical group and 49.9, 61.8 and 43.4%, respectively, in the non-surgical group. The favorable impact of primary surgical treatment on oncologic outcomes was statistically significant after multivariate analysis. This effect was more marked for locally-advanced than for early-stage tumors. Propensity score matching analysis confirmed the prognostic impact of primary surgical treatment for RFS. Conclusion: Therapeutic strategy is an independent prognostic factor in patients with p16-negative OPSCC and primary surgical treatment is associated with improved OS, DSS and RFS. These results suggest that surgical strategy is a reliable option for advanced stage OPSCC.